Peer-Mediated Intervention for the Development of Social Interaction Skills in High-Functioning Autism Spectrum Disorder: A Pilot Study - Rodríguez-Medina, Jairo; Martín-Antón, Luis J.; Carbonero, Miguel A.; Ovejero, Anastasio (Frontiers in Psychology, 2016)
Autism Spectrum Disorder (ASD) is characterized by difficulties with social interaction and communication, which manifest at school especially in less structured situations such as recess. Recess provides opportunities for relationship with peers in a natural context, for which students with ASD may not be equipped with the necessary skills to use without support. Using a single-case design, we evaluated an intervention applied in recess to improve the social interaction skills of a student with high-functioning ASD mediated by his peers without ASD, in second grade of elementary school. This intervention includes different strategies to initiate the peers without ASD, using direct instruction, modeling, and social reinforcement carried out in the recess setting. After 14 sessions, changes were observed in the rates of initiating and responding to interactions, and a negative trend in the percentage of time that the student maintained low-intensity interactions or was alone. Teachers and family perceived improvements in social skills, more peer acceptance, and increase in the frequency and duration of social interactions. This intervention can help teachers to apply research-based practices to improve some social interaction skills in high-functioning students with autism in inclusive school environments.